2007
DOI: 10.1073/pnas.0703410104
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β-deficient female mice develop a bladder phenotype resembling human interstitial cystitis

Abstract: Interstitial cystitis/painful bladder syndrome is a disease seen mostly in women, and symptoms tend to be worse premenopausally or during ovulation. The four cardinal symptoms of interstitial cystitis/painful bladder syndrome are bladder pain, urgency, frequency, and nocturia. Estrogen has been implicated in the etiology of this disease, but the role of the two estrogen receptors (ER), ER␣ and ER␤, has not been investigated. We found that, in the bladders of WT mice, ER␤ is expressed in the basal cell layer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
(36 reference statements)
1
36
0
1
Order By: Relevance
“…For example, ER␤ (female) null mice exhibit urinary bladder alterations that have also been associated with BPS/IC in humans (143). There is also a naturally occurring disease in cats termed feline interstitial cystitis (FIC), which shares nearly all the characteristics of the nonulcerative form of BPS/IC found in humans (53,295).…”
Section: A Bladder Pain Syndromementioning
confidence: 99%
“…For example, ER␤ (female) null mice exhibit urinary bladder alterations that have also been associated with BPS/IC in humans (143). There is also a naturally occurring disease in cats termed feline interstitial cystitis (FIC), which shares nearly all the characteristics of the nonulcerative form of BPS/IC found in humans (53,295).…”
Section: A Bladder Pain Syndromementioning
confidence: 99%
“…In contrast, the bladder of females and colon of both sexes of young ER␤KO KI have been reported to display defects that correct with aging (24,25). More specifically, in young female ER␤KO KI mice, the bladder was reported to develop features resembling human interstitial cystitis in females (25) and, in both sexes, the colon exhibited severe subepithelial lymphoid infiltrates predominantly in its proximal portion and an abnormal mucin distribution in its distal portion (24). We conclude that the bladder and colon of our ER␤ ST LϪ/LϪ mutants lack the morphological abnormalities that were found in young ER␤KO KI mutants.…”
Section: The Er␤st L؊/l؊ Urinary Bladder and Colon Display A Normal Smentioning
confidence: 99%
“…To eliminate any possible phenotypic effect of these transcript variants, we decided to generate an ER␤-null mutant, hereafter referred to as ER␤ ST LϪ/LϪ , in which exon 3 was deleted through Cre/LoxP-mediated excision and which was devoid of any transcript downstream of exon 3. We report here the characterization of these ER␤ ST LϪ/LϪ mutants, which do not display morphological defects in the prostate, in contrast to ER␤KO CH and ER␤KO KI mutants (13,16,19), or, in contrast to ER␤KO KI mutants, defects in the brain (17), lymphoid tissues (20), heart (21), lung (22,23), colon (24), and urinary bladder (25).…”
mentioning
confidence: 99%
“…Indeed, in the bladder of rats with chemically induced cystitis, a significant reduction of estrogen receptor b (ERb) has been found [7]. Moreover, female ERb null mice exhibit urinary bladder alterations that resemble those associated with IC/BPS in humans [8], whereas Cabral et al showed that estrogen deficiency may also lead to bladder wall stiffness, by decreasing some components of the extracellular matrix in female rat urothelial surface [9].…”
Section: Introductionmentioning
confidence: 98%